Sex differences in expression of CGRP family of receptors and ligands in the rat trigeminal system - Aida Maddahi; Jacob C. A. Edvinsson; Lars Edvinsson (The Journal of Headache and Pain)
Abstract Background Calcitonin gene-related peptide (CGRP) is part of the calcitonin peptide family, which includes calcitonin (CT), amylin (AMY), and adrenomedullin (ADM). CGRP and its receptor are highly present in the trigeminovascular system (TVS). Recent research suggests that other members of the calcitonin family could be feasible therapeutic targets in the treatment of migraine. The present study aims to elucidate the distribution of ADM, AMY, CT, and their receptors in the rat TVS, and to explore potential sex differences in their expression. Methods Trigeminal ganglia (TG) were dissected from male and female adult rats. Protein and gene expression were assessed through immunohistochemistry and RT-qPCR. Additionally, the dura mater was isolated for further investigation of protein expression and fiber localization using immunohistochemistry. Results Quantitative gene expression analysis revealed the presence of all genes in male and female TGs, except for calcitonin receptor (CTR). Notably, CGRP mRNA levels in TG were several folds higher than those of other genes. The receptor activity-modifying protein-1 (RAMP1) mRNA levels were significantly higher in female compared to male. No AMY or CT immunoreactivity was observed in the TVS. In contrast, immunoreactivity for ADM, CGRP, RAMP1, CTR, and calcitonin-like receptor (CLR) were observed in the cytoplasm of TG neurons. Immunoreactive Aδ-fibers storing RAMP1, ADM and CLR were also identified. RAMP2 and RAMP3 were expressed in nucleus of TG neurons and in satellite glial cells. Furthermore, RAMP1 and CLR were co-localized with CASPR in the nodes of Ranvier located in Aδ-fibers. Conclusions This study provides valuable insights into the distribution of the CGRP family of peptides and their receptors in the TVS. CGRP mRNA levels in the TG were markedly higher than those of other genes, demonstrating the key role of CGRP. The co-localization of CLR and RAMP1 on Aδ-fibers with CASPR suggests a potential role for this receptor in modulating trigeminal nerve function and neuronal excitability, with implications for migraine pathophysiology. Additionally, RAMP1 mRNA levels were significantly higher in female TG compared to males, indicating sex-specific differences in gene expression. These findings underscore the need for further research into the functional significance of gender-related variations.